Experimental procedure and simplified modeling for the high strain-rate and transient hardness evolution of aluminum AA1050. (July 2018) - dos Santos, Tiago; Rossi, Rodrigo; Maghous, Samir; Rosa, Pedro A.R.
Highlights: High strain-rate experimental characterization of aluminum AA1050 is performed. Specific experiments reveal the past strain-rate influence on hardness evolution. A constitutive model predicting the experimental behavior is developed. Proposed modeling accounts for deformation history effects on the hardness evolution. Constitutive model is calibrated and validated against experimental results. Abstract: This work investigates the strain-rate influence on Vickers hardness evolution of a commercially pure aluminum (AA1050). The material hardness properties are assessed by means of laboratory tests employing quasi-static indentation tests performed on samples previously submitted to dynamic plastic compression considering a wide range of strain and strain-rate levels. Total strains of approximately 1.5 are imposed at different strain-rates, ranging from quasi-static to high strain-rate ( 1.1 × 10 4 s − 1 ) conditions. The experiments consist of nearly constant strain-rate incremental compressions, decremental strain-rate and strain-rate jump tests. High strain-rate tests are conducted employing a specifically designed impact testing machine. It is observed that both the material hardness and the corresponding hardening-rate increase with loading-rate. However, strain-rate effects are more pronounced at earlier deformations stages. Specific experiments with abrupt (decremental or jump) changes in strain-rate reveal the loading path influence on corresponding material hardness evolution. Specifically, short inverted transients are evidenced from decremental tests. In order to macroscopically describe the experimental material hardness behavior in terms of strain and strain-rate histories, a single scalar internal variable model is formulated. The associated model parameters are calibrated using constant strain-rate experimental data, and the model validation is performed against sequential strain-rate experiments. Overall, the model performs reasonable well within considered strain and strain-rate ranges, while remaining tractable for material identification procedure. However, the inverted transient response observed in decremental tests is not fully well captured, which is clearly a counterpart of operating with a single variable approach. Additionally, the employed methodology can be viewed as an easy-to-perform and low-cost procedure to macroscopically assess the corresponding yield stress and hardening behavior of a metallic material at high strain-rate, since expensive instrumentation and high speed data acquisition systems are not necessary. Its effectiveness will rely on the ability to formulate and calibrate constitutive or empirical correlations between the current yield stress and corresponding material hardness.